2023
DOI: 10.1177/17571774231152719
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use among paediatric inpatients in a Nigerian tertiary hospital: A three-year point prevalence survey

Abstract: Aim Antimicrobials are among the most widely prescribed therapeutic agents among paediatric population. Irrational use of these agents increases the risk of antimicrobial resistance. We described the prevalence and pattern of antimicrobial use among paediatric inpatients from 2017 to 2019. Subject and Method The study was a repeated point prevalence survey over a 3-year period using the global point prevalence standardized tools among all paediatric inpatients. The prevalence of antimicrobial use, the prescrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…It is noteworthy that most of the patients who had inappropriate choice of antibiotics were placed on multiple antibiotics when the guidelines recommended a single antibiotic. This is similar to other studies done in Nigeria which showed high usage of multiple antibiotic therapy (26). The use of, multiple antibiotic therapy, especially those with similar antibiotic spectrum, results in redundant therapy which could lead to increased costs, increased risk of adverse effects and antago-nism and the development of resistance (27).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It is noteworthy that most of the patients who had inappropriate choice of antibiotics were placed on multiple antibiotics when the guidelines recommended a single antibiotic. This is similar to other studies done in Nigeria which showed high usage of multiple antibiotic therapy (26). The use of, multiple antibiotic therapy, especially those with similar antibiotic spectrum, results in redundant therapy which could lead to increased costs, increased risk of adverse effects and antago-nism and the development of resistance (27).…”
Section: Resultssupporting
confidence: 86%
“…Most of the point prevalence surveys of antimicrobial consumption in Nigeria have shown ceftriaxone and metronidazole as the most commonly prescribed antibiotics in tertiary healthcare facilities like ours (13,26). Similarly, a study done in Uganda showed that the most frequently prescribed antibiotics for in-patients were ceftriaxone (66%), metronidazole (41%), co-trimoxazole (27%), ciprofloxacin (19.0%) and amoxicillin (10.0%) (28).…”
Section: Resultsmentioning
confidence: 98%